Pattern of chilblains in a high altitude region of Ladakh, India - Singh, G.K. (Med J Armed Forces India, 2015)
BACKGROUND: Extreme sub-zero temperature in winters (15 °C to −25 °C), high velocity winds and wind-chill factor pose risk to those who resides at the high altitude environment to develop cold related injuries like chilblains and frostbite. The aim of this study was to study the patterns of chilblains in high altitude region like Ladakh. METHODS: The study was conducted at Dermatology outpatient department of Military Hospital, Leh from 1 Sep 2009 to 31 May 2010. Patients, satisfying clinical criteria for the diagnosis of chilblains were included into the study. Detailed history and thorough clinical examination was conducted. Complete blood count and Urine routine examination was carried out in every patient. Anti Nuclear Factor tests were carried out in only those who had history suggestive of connective tissue disease. RESULTS: Total 108 (5.75%) were diagnosed to have chilblains. Only a single case of chilblain was found in a local resident (p < 0.005). Family history of chilblains was present in 10 (9.2%) patients, there was recurrence in 12 (11.1%) and 21 patients (19.4%) were smokers. Most (63.8%) of the patients, had BMI between 20 and 22 kg/m(2) (mean = 20.03 kg/m(2); 95% CI = 19.68–20.38 and SD 1.82). 42.1% of cases of chilblains also had hyperhidrosis (p < 0.05). CONCLUSION: In a HA area like Ladakh, the non-natives suffer maximum from chilblains. This could be explained by the protective genetic adaptability of natives to extreme cold environment and their protective life style against cold. Low body mass index (BMI) and hyperhidrosis are important associations for development of chilblains.